DIPLOMASI KEBUDAYAAN INDONESIA TERHADAP KAZAKHSTAN MELALUI PENCAK SILAT TAHUN 2019-2023 - Huda, Syabbul; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research delineates Indonesia's cultural diplomacy through Pencak Silat towards Kazakhstan from 2019 to 2023. Pencak Silat, an indigenous martial art, represents a cultural heritage of Indonesia. Pencak Silat has undergone rapid development and dissemination to foreign countries, including Kazakhstan. Kazakhstani society has adopted Pencak Silat as a fundamental martial art and has achieved success in various Pencak Silat competitions. This phenomenon is a result of Indonesia's efforts to promote Pencak Silat to Kazakhstan as a form of cultural diplomacy. This qualitative descriptive study employs literature review as the primary method of data collection, drawing from books, journals, websites, and relevant documents. The research framework incorporates the perspectives of Liberalism, Cultural Diplomacy theory, and the concept of National Interest. The findings of this study elucidate how Pencak Silat, as an Indonesian cultural heritage, serves as a medium for cultural diplomacy between Indonesia and Kazakhstan, strengthening bilateral relations and advancing Indonesia's national interests. Keywords: Pencak Silat, Diplomacy, Culture, National Interest, Indonesia, Kazakhstan, Sports, Bilateral Relations.